The Impact of Mpox on Children's Health: A Comprehensive Overview - Andariska, Ni Made Gita (Jurnal KESANS : Kesehatan dan Sains, 2024)
Mpox (formerly monkey pox) is an emerging zoonotic disease caused by infection with the Mpox virus, which affects both humans and animals. The disease is usually self-limiting, but severe illness can occur in certain groups especially children, and people who are immunocompromised or pregnant. In recent years, rapid globalization, population movement and deepening trade networks have contributed to the international spread of Mpox, resulting in outbreaks in various countries around the world. Based on information from previous outbreaks, children may be more susceptible to severe manifestations of the disease, leading to sepsis, encephalitis, and even death or long-term disability. In addition, the reports recommends that babies born to mothers who had Mpox virus while pregnant should be properly monitored in specialized care facilities. This overview presents a thorough review of Mpox, including its transmission patterns, epidemiology and pathogenesis. This review aims to provide updated information about Mpox virus for designing better treatment.